2014
DOI: 10.4238/2014.december.12.10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic diversity of Chinese native Cannabis sativa cultivars by using ISSR and chromosome markers

Abstract: ABSTRACT. Hemp (Cannabis sativa) is an important fiber crop, and native cultivars exist widely throughout China. In the present study, we analyzed the genetic diversity of 27 important Chinese native hemp cultivars, by using inter-simple sequence repeats (ISSR) and chromosome markers. We determined the following chromosome formulas: 2n = 20 = 14m + 6sm; 2n = 20 = 20m; 2n = 20 = 18m + 2sm; 2n = 20 = 16m + 4sm; and 2n = 20 = 12m + 8sm. The results of our ISSR analysis revealed the genetic relationships among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…Heterozygosity indicates levels of genetic diversity within populations, and has also been used to estimate genetic distance between populations 49 , 50 . Consistent with genetic diversity levels in the present study, previous estimates of heterozygosity across diverse marker types (e.g., SNP, SSR, AFLP) typically identify higher levels of heterozygosity in hemp compared to marijuana 30 , 51 53 . However, it should be noted that one study found lower levels of heterozygosity in hemp varieties across 195 samples and 2894 SNPs 29 .…”
Section: Discussionsupporting
confidence: 89%
“…Heterozygosity indicates levels of genetic diversity within populations, and has also been used to estimate genetic distance between populations 49 , 50 . Consistent with genetic diversity levels in the present study, previous estimates of heterozygosity across diverse marker types (e.g., SNP, SSR, AFLP) typically identify higher levels of heterozygosity in hemp compared to marijuana 30 , 51 53 . However, it should be noted that one study found lower levels of heterozygosity in hemp varieties across 195 samples and 2894 SNPs 29 .…”
Section: Discussionsupporting
confidence: 89%
“…A number of genetic markers have been used to determine levels of heterozygosity in Chinese Cannabis germplasm (Table 1 ), with SSR, amplified fragment length polymorphism (AFLP) and randomly amplified polymorphic DNA (RAPD) genetic markers indicating a high level of genetic diversity, with the proportion of polymorphic loci ranging from 75 to 92% (Gilmore et al, 2007 ; Hu et al, 2012 ; Gao et al, 2014 ; Zhang et al, 2014 ). Analysis of 76 accessions from 26 countries using 12 chloroplast and mitochondrial DNA loci revealed six haplotypes, all of which were located within or adjacent to China (Gilmore et al, 2007 ).…”
Section: A Hypervariable Species Shaped By Domesticationmentioning
confidence: 99%
“…The long and close association of Cannabis plant with man has caused high variations. Today, in China the ancient cultivation of Cannabis results in genetically distinct regional varieties of fiber‐rich hemp that are adapted to local environmental conditions throughout the country (Gao et al, ; Zhang et al, ). The Cannabis smell is a peculiarity of this plant.…”
Section: Introductionmentioning
confidence: 99%